Green investment and firm value: Does corporate governance matter? - Estu Widarwati; Nabila Nur Rohmah; E Wityasminingsih; Nunik Nurmalasari; Devy Widya Apriandi; Mutqi Sopiawadi (Journal of Accounting and Investment, 2024)
Research aims: This study examines the effect of green investment on firm value with corporate governance moderation.Design/Methodology/Approach: Green investment is proxied by the green-firm investment ratio, Tobin's Q measures firm value, and corporate governance is proxied by board size. The sample is 34 companies receiving PROPER awards listed on the IDX for the 2017-2021 period from the primary material, consumer non-cyclical, and consumer cyclical sectors. The data were analyzed using panel data regression, T-test, and moderate regression analysis tests.Research findings: The results showed that green investment positively affects firm value. Meanwhile, this study has not found strong evidence about the moderation role of board size in the effect of green investment and firm value.Theoretical contribution/Originality: This research strengthened previous empirical evidence that companies' implementation of green investment activities will impact increasing firm value and board size as part of effective governance needs to be paid attention.Practitioner/Policy implication: This research has implications for companies to include green investment as an important investment decision because it is proven to be an advantage for companies to increase their valueResearch limitation/Implication: This research's determining factor for firm value is only green investment, and the corporate governance proxy only uses board size. Therefore, it is hoped that future research can explore other new models that consider industry characteristics, economic conditions in the research period, and other measures of the variables studied.